Lewis acid coordination polymer and its preparation method and application
By reacting polyamine derivatives with metal ion Lewis acid to generate metal coordination polymers as cathode modification layer, the problems of high-temperature preparation of cathode modification layer materials and degradation of non-fullerene receptors in the prior art are solved, and high efficiency and stability are achieved photoelectric conversion performance and thickness tolerance of solar cells.
Patent Information
- Application Number
- CN202310128897.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-02-07
AI Technical Summary
In existing organic solar cells, cathode modification layer materials are prepared at high temperatures, which cannot meet the needs of low-temperature printing to prepare flexible solar cells. Moreover, the photoelectric conversion efficiency of common materials decreases when the thickness is thick, and contains primary amine, secondary amine, and tertiary amine functional groups. This leads to the degradation of non-fullerene receptor molecules and reduces the photoelectric conversion performance.
The polyamine derivative reacts with the metal ion Lewis acid containing the empty track to generate the Lewis acid coordination polymer, reduce the content of amine functional groups, and form the metal coordination polymer as the cathode modification layer, and is prepared by spin coating, spraying, and printing processes. Avoid high temperature treatment.
The cathode modification layer is prepared at low temperature, which improves the photoelectric conversion efficiency and stability of solar cells, inhibits the degradation of non-fullerene receptors, and is suitable for reverse and forward organic solar cells, with good thickness tolerance. and industrial production potential.
Smart Images

Figure CN116041698B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solar cells, and in particular to a Lewis acid coordination polymer and a preparation method and application thereof. Background Art
[0002] With the progress of the times, the continuous development of economy and science and technology, our demand for energy is still increasing. Developing a renewable resource that is abundant, low-cost and environmentally friendly has become a hot topic for people to explore and study. Among them, solar cells can convert solar energy into electrical energy, have great application potential, and are one of the hottest research areas in recent years. Compared with other types of solar cells, organic solar cells (OSCs) and perovskite solar cells (PSCs) have attracted widespread attention due to their wide range of material sources, light texture, easy processing, indoor energy collection, translucency, large-scale printing and flexibility, showing great commercial application prospects.
[0003] The interface layer is between the photoactive layer and the electrode, and has the functions of adjusting the work function, reducing the energy barrier, and promoting the transfer of electrons or holes. Among them, the interface layer used to block holes, extract and transfer electrons is called the cathode modification layer (CILs), which is also one of the keys to the development of high-performance OSCs. When the anode modification layer is covered on the transparent indium tin oxide conductive glass positive electrode, the OSCs device is a forward device structure; when the cathode modification layer is covered on the transparent indium tin oxide conductive glass negative electrode, the OSCs device is a reverse device structure. Zinc oxide is a representative inorganic metal semiconductor cathode modification layer, but the use of inorganic metal semiconductors to prepare high-performance solar cell devices often requires high-temperature annealing above 200°C, which cannot meet the needs of large-area printing to prepare flexible solar cell devices in the future. Therefore, in order to meet the needs of preparing flexible solar cell devices by low-temperature printing or spraying processes, it is necessary to develop cathode modification layer materials with large thickness tolerance, heat treatment temperature below 100°C and low cost, which is one of the key contents of this research field at present.
[0004] To this end, researchers have developed a series of organic small molecule CILs and polymer CILs. At present, CILs for high-performance OSCs are generally based on organic small molecules or polymers of perylene diimide, polyfluorene, and polynaphthalene diimide derivatives. These materials generally also contain amine or quaternary ammonium salt functional groups. However, there are two shortcomings of the materials here: on the one hand, this type of material has a conjugated macrocyclic structure. Although this type of conjugated unit can improve the electron mobility of the material, it also makes this type of material more suitable for use in forward OSCs devices. Once applied to reverse OSCs devices, due to the light absorption characteristics of the CILs themselves, the light absorption capacity of the photoactive will be reduced, thereby limiting the photocurrent efficiency of the OSCs; on the other hand, the synthesis of this type of material is relatively complex and the cost is high, which is not conducive to practical application. Therefore, we previously obtained cheap polymer CILs by reacting polyethyleneimine derivatives with dihaloalkanes or disulfonate diols (ZL 201710654169.2, ZL 202010001049.4), and obtained polymer CILs by reacting polyamine derivatives with dihaloalkanes or disulfonate diols (ZL202010001043.7). These CILs showed excellent performance and good thickness tolerance in fullerene-based OSCs, and their films also showed good performance in non-fullerene-based OSCs. However, when the thickness of these CILs was thicker, the photoelectric conversion efficiency of the OSCs decreased rapidly, and the photoelectric conversion efficiency of the OSCs device decayed quickly, which was not conducive to the application of OSCs.
[0005] Recently, it has been reported that PEIE containing primary and secondary amines can cause degradation of non-fullerene acceptor molecules (Adv. Energy Sustainability Res, 2021, 2, 2000094). In our previous studies, we found that triethylamine can cause degradation of non-fullerene acceptor molecules ITIC, while quaternary ammonium salts do not cause ITIC degradation. Therefore, the non-conjugated polymer PEDETA-DBO generated by the reaction of pentahydroxyethyldiethylenetriamine and 1,8-dibromooctane, due to the residual tertiary amine groups in the polymer, will cause the degradation of non-fullerene acceptor molecules (J. Mater. Chem. A, 2021, 9, 22926-22933), which leads to the degradation of the photoelectric conversion performance and stability of the reverse non-fullerene OSCs based on PEDETA-DBO. In addition, the currently used organic small molecule CILs and polymer CILs generally contain primary amines, secondary amines, tertiary amines and other functional groups in order to improve the conductivity of CILs by doping. The presence of these Lewis bases will also lead to the degradation of non-fullerene acceptor molecules, thereby reducing the photoelectric conversion efficiency and stability of OSCs. Especially in reverse OSCs, this negative impact will be more obvious.
[0006] Therefore, finding a way to improve the performance of organic small molecule CILs and polymer CILs and inhibit the degradation of non-fullerene acceptors will surely accelerate the pace of OSCs application. It is particularly important to develop such CILs materials and obtain independent intellectual property rights to ensure the leading position in this field. Summary of the invention
[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a Lewis acid coordination polymer and a preparation method and application thereof. The Lewis acid coordination polymer is used as a cathode modification layer by reacting a polyamine derivative with a metal ion Lewis acid containing an empty orbital to obtain a coordination compound, or by coordinating a polymer containing an amine functional group with a metal ion Lewis acid containing an empty orbital to form a metal coordination polymer. The coordination reaction reduces the content of the amine functional group in the solution, thereby shielding the degradation of non-fullerene receptor molecules induced by the amine functional group.
[0008] In order to solve the above technical problems, the technical solution of the present invention is as follows:
[0009] A Lewis acid coordination polymer is obtained by reacting a polyamine organic small molecule or a polymer containing an amine functional group with a Lewis acid, wherein the Lewis acid is a metal ion compound containing an empty orbital, and its molecular structure includes one or more of the structural formulas shown in formula (I), formula (II), formula (III), formula (IV), formula (V), formula (VI), formula (VII), formula (VIII) and formula (IX);
[0010]
[0011]
[0012] In the structural formulas represented by formula (I), formula (II), formula (III), formula (IV), formula (V), formula (VI), formula (VII), formula (VIII) and formula (IX), ML z Wherein M is a metal cation containing an empty orbital, M is selected from one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Ge, Sr, Y, Zr, Nb, Mo, Tc, Pd, Ru, Ag, Au, Cd, In, Sn, Sb, Cs, Ba, W, Pt, Tl, Pb, Hf, La, Sm and Eu cations, but is not limited to the listed atoms; L is one or more of fluoride ion, chloride ion, bromide ion, iodide ion, sulfonate, acetate, sulfate, carbonate, nitrate, phosphate and hydroxide ion, but is not limited to the listed anions; Z is the number of ionic bonds or coordination bonds between the metal cation M and the anion L, and the value is one of 1 to 4; CA is selected from one or more of alkanes with 2 to 15 carbon atoms or alkanes containing aromatic rings, and X -One or more selected from fluoride ion, chloride ion, bromide ion, iodide ion, sulfonate, acetate, sulfate, carbonate, nitrate, phosphate and hydroxide ion, but not limited to the listed ions, R is selected from one or more of H, CH3, CH2CH3, CH2OH and C2H4OH, R1 is selected from one or more of H, CH3, CH2CH3, CH2OH and C2H4OH, R2 is selected from one or more of H, CH3, CH2CH3, CH2OH and C2H4OH, R3 is selected from one or more of H, CH3, CH2CH3, CH2OH and C2H4OH, n, a, b, c are degrees of polymerization, selected from any number between 5 and 500.
[0013] As a general technical concept, the present invention also provides a method for preparing the above-mentioned Lewis acid coordination polymer, wherein the Lewis acid coordination polymer is obtained by reacting a polyamine derivative with a Lewis acid;
[0014] The polyamine derivatives are N-methylethylenediamine, N-ethylethylenediamine, N1,N2-dimethylethylenediamine, N-(2-hydroxyethyl)ethylenediamine, N,N-bis(2-hydroxyethyl)ethylenediamine, N,N,N,N-tetra(2-hydroxyethyl)ethylenediamine, piperazine, N,N-dimethylpiperazine, N,N-bis(2-hydroxyethyl)piperazine, tetramethylmethanediamine, N1,N2,N3-trimethyldiethylenetriamine, tris(2-dimethylaminoethyl)amine, N,N,N-tris(2-hydroxyethyl)hexahydro-s-triazine, 2,4,6-trimethyl-1,3,5-triazine , one or more of N1,N1,N2,N2-tetramethylethylenediamine, N1,N1,N2,N2-tetraethylethylenediamine, N1,N1,N2,N2-tetra(2-hydroxyethyl)ethylenediamine, pentamethyldiethylenetriamine, pentaethyldiethylenetriamine, penta(2-hydroxyethyl)diethylenetriamine, hexamethyltriethylenetetramine, hexaethyltriethylenetetramine, hexa(2-hydroxyethyl)triethylenetetramine, heptamethyltetraethylenepentamine, heptaethyltetraethylenepentamine and heptath(2-hydroxyethyl)tetraethylenepentamine, polyethyleneimine and polyethoxyethyleneimine, but not limited to the listed compounds;
[0015] The Lewis acid refers to a metal ion compound that can form a coordination bond with the lone pair of electrons on the nitrogen atom in the amine derivative and has an empty orbital. The structural formula of the Lewis acid is one or more of ML, ML2, ML3 and ML4, wherein M is selected from one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Ge, Sr, Y, Zr, Nb, Mo, Tc, Pd, Ru, Ag, Au, Cd, In, Sn, Sb, Cs, Ba, W, Pt, Tl, Pb, Hf, La, Sm and Eu cations, but is not limited to the listed ions, and L is one or more of fluoride, chloride, bromide, iodide, sulfonate, acetate, sulfate, carbonate, nitrate, phosphate and hydroxide ions, but is not limited to the listed ions.
[0016] The above-mentioned Lewis acid coordination polymers correspond to formula (I), formula (II), formula (III), formula (IV), and formula (V).
[0017] The method for preparing the above-mentioned Lewis acid coordination polymer preferably comprises the following steps:
[0018] S1. diluting the polyamine derivative according to claim 2 with an alcohol solvent to obtain a solution; wherein the alcohol solvent is one or more of methanol, ethanol, 2-methoxyethanol, 1-propanol, isopropanol, 1-butanol and t-tert-butanol;
[0019] S2. Add Lewis acid to the solution obtained in S1, and stir the reaction at 40° C. to 90° C. for 4 h to 72 h to obtain a final Lewis acid coordination polymer solution.
[0020] In the above-mentioned method for preparing Lewis acid coordination polymer, preferably, the mass fraction of the polyamine derivative in the solution is 0.01% to 5%; the molar ratio of the amine in the polyamine derivative to the Lewis acid is 100:1-100.
[0021] As a general technical concept, the present invention also provides a method for preparing the above-mentioned Lewis acid coordination polymer, wherein the Lewis acid coordination polymer is obtained by reacting a polyelectrolyte containing both amine and quaternary ammonium salt functional groups with a Lewis acid;
[0022] The polyelectrolyte comprises one or more of the following formulas X, XI, XII and XIII,
[0023]
[0024] Wherein, CA is selected from one or more alkanes having 2 to 15 carbon atoms or alkanes containing aromatic rings, and X -One or more selected from fluoride, chloride, bromide, iodide, sulfonate, acetate, sulfate, carbonate, nitrate, phosphate and hydroxide ions, but not limited to the listed ions, R is selected from one or more selected from H, CH3, CH2CH3, CH2OH and C2H4OH, R1 is selected from one of H, CH2CH2NH2 and CH2CH2OH, R2 is selected from one of H, CH2CH2NH2 and CH2CH2OH, R3 is selected from one of H, CH2CH2NH2 and CH2CH2OH, 5≤a≤500, 5≤b≤500, 5≤c≤500;
[0025] The Lewis acid refers to a metal ion compound that can form a coordination bond with the lone pair of electrons on the nitrogen atom in the amine derivative and has an empty orbital. The structural formula of the Lewis acid is one or more of ML, ML2, ML3 and ML4, wherein M is selected from one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Ga, Ge, Sr, Y, Zr, Nb, Mo, Tc, Pd, Ru, Ag, Au, Cd, In, Sn, Sb, Cs, Ba, W, Pt, Tl, Pb, Hf, La, Sm and Eu cations, but is not limited to the listed ions, and L is one or more of fluoride, chloride, bromide, iodide, sulfonate, acetate, sulfate, carbonate, nitrate, phosphate and hydroxide ions, but is not limited to the listed ions.
[0026] The above-mentioned Lewis acid coordination polymers correspond to formula (VI), formula (VII), formula (VIII) and formula (IX). Among the above-mentioned polyelectrolytes, formula X corresponds to formula (VIII), formula XI corresponds to formula (VII), formula XII corresponds to formula (IX), and formula XIII corresponds to formula (VI).
[0027] The method for preparing the above-mentioned Lewis acid coordination polymer preferably comprises the following steps:
[0028] S1, first preparing an alcohol solution of a polyelectrolyte of formula X, formula XI, formula XII or formula XIII, wherein the alcohol solvent used is one or more of methanol, ethanol, 2-methoxyethanol, 1-propanol, isopropanol, 1-butanol and t-tert-butanol;
[0029] S2. Add Lewis acid to the alcohol solution of the polyelectrolyte obtained in S1, and stir the reaction at 40° C. to 90° C. for 4 h to 72 h to obtain a final Lewis acid coordination polymer solution.
[0030] In the above-mentioned method for preparing Lewis acid coordination polymer, preferably, the mass fraction of the polyelectrolyte is 0.01% to 5%; the mass ratio of the polyelectrolyte to the Lewis acid is 100:0.1-100.
[0031] As a general technical concept, the present invention also provides a use of the above-mentioned Lewis acid coordination polymer or the Lewis acid coordination polymer prepared by the above-mentioned preparation method in an organic solar cell or a perovskite solar cell.
[0032] In the above application, preferably, when the organic solar cell is an inverted organic solar cell, the application comprises the following steps: applying the Lewis acid coordination polymer dissolved or diluted in an alcohol solvent on a transparent conductive electrode by spin coating, heating at a temperature of 50 to 120° C. for 5 to 10 minutes or heating at 10 -2 ~10 2 Pa conditions for 0.5 to 3 hours to obtain an electrode coated with a cathode modification layer; further coating a photoactive layer material and an anode modification layer on the cathode modification layer; and then coating a metal electrode by evaporation to finally obtain a reverse organic solar cell;
[0033] When the organic solar cell is a forward organic solar cell, the application comprises the following steps: applying a photoactive layer material to a transparent conductive electrode modified by an anode modification layer, then applying a Lewis acid coordination polymer dissolved or diluted in an alcohol solvent to the photoactive layer material by spin coating as a cathode modification layer, -2 ~10 2 Pa conditions for 0.5 to 3 hours to remove the alcohol solvent, and then evaporate the metal electrode to obtain a forward organic solar cell.
[0034] In the above application, preferably, the preparation of the perovskite solar cell comprises the following steps: applying the coordination polymer dissolved or diluted in an alcohol solvent on a transparent conductive electrode by spin coating, heating at 50 to 120° C. for 5 to 10 minutes or heating at 10 -2 ~10 2 Pa conditions for 0.5 to 3 hours to obtain an electrode modified with a cathode modification layer; coating a perovskite photoactive layer on the modified cathode, and then coating an anode modification layer and evaporating a metal electrode to obtain a nip-type perovskite solar cell;
[0035] The preparation of perovskite solar cells includes the following steps: coating the perovskite photoactive layer material on the transparent conductive electrode modified by the anode modification layer, then coating the cathode modification layer material dissolved or diluted by an alcohol solvent on the active layer material by spin coating or printing, and evaporating the metal electrode to obtain a pin-type perovskite solar cell.
[0036] Compared with the prior art, the advantages of the present invention are:
[0037] (1) The coordination polymer provided by the present invention has a simple preparation process and does not require high temperature treatment. The cathode modification layer can be prepared by spin coating, spray coating, or printing, which is conducive to large-scale industrial production.
[0038] (2) The coordination polymer provided by the present invention can still ensure that the solar cell has a high photoelectric conversion efficiency at a thickness of 30 nm.
[0039] (3) The coordination polymer provided by the present invention can inhibit the degradation of non-fullerene acceptors, so that the photoelectric conversion efficiency of solar cells can remain stable for a long time. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 It is a JV curve diagram of the THEED-DBO-Pt and reverse OSCs devices with different photoactive layers based on Example 9 of the present invention.
[0041] Figure 2 It is a JV curve diagram of the forward OSCs devices based on THEED-DBO-Pt of Example 9 of the present invention and different photoactive layers.
[0042] Figure 3 It is a JV curve diagram of the reverse OSCs device based on THEED-DBO-Pt of Example 9 of the present invention with different thicknesses.
[0043] Figure 4 It is a curve chart of the photoelectric conversion efficiency of the reverse OSCs device based on THEED-DBO-Pt of Example 9 of the present invention, ZnO of Comparative Example 1, and THEED-DBO of Comparative Example 2 versus storage time. DETAILED DESCRIPTION
[0044] The present invention will be further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the scope of protection of the present invention is not limited thereto. The following embodiments are intended to facilitate the understanding of the present invention and do not have any limiting effect on them. The methods are conventional methods unless otherwise specified, and the reaction materials can be purchased from public commercial channels unless otherwise specified.
[0045] Embodiment 1:
[0046] A Lewis acid coordination polymer THEED-Pt of the present invention is obtained by reacting N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine with platinum dichloride (PtCl2), and the reaction equation is:
[0047]
[0048] Among them, 5≤n≤500.
[0049] In this embodiment, the preparation method of THEED-Pt includes the following steps:
[0050] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless and transparent solution with a mass concentration of 2%.
[0051] (2) Add 2.0 mg of platinum dichloride to the solution so that the molar ratio of THEED to platinum dichloride is 22.6:1, and heat and stir at 70° C. for 5 hours to obtain a colorless solution of Lewis acid coordination polymer THEED-Pt.
[0052] The method for preparing the Lewis acid coordination polymer THEED-Pt as a cathode modification layer is specifically as follows:
[0053] (1) In actual operation, cathode modification layer films of different thicknesses are obtained by controlling the concentration of the solution. When the concentration of THEED-Pt in the solution is 0.1%, the thickness of the prepared THEED-Pt film is about 10 nm. The OSCs device prepared at this thickness can achieve the best photoelectric conversion efficiency, so this concentration solution is used as the cathode modification layer in the following examples.
[0054] (2) In actual operation, the 2% THEED-Pt solution was first diluted to 0.1%, and about 70 μL of 0.1% THEED-Pt was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm. The spin coating time was 50 s. After the spin coating was completed, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0055] Embodiment 2:
[0056] A Lewis acid coordination polymer THEED-Ag of the present invention is obtained by reacting N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine with silver nitrate (AgNO3), and the reaction equation is:
[0057]
[0058] Among them, 5≤n≤500.
[0059] In this embodiment, the preparation method of Lewis acid coordination polymer THEED-Ag is:
[0060] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless and transparent solution with a mass concentration of 2%.
[0061] (2) 1.3 mg of silver nitrate was added to make the molar ratio of THEED to silver nitrate be 22.1:1, and the mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of the complex THEED-Ag.
[0062] The method for preparing the THEED-Ag complex as a cathode modification layer is specifically as follows:
[0063] In actual operation, the 2% THEED-Ag solution was first diluted to 0.1%, and then about 70 μL of the 0.1% THEED-Ag complex was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating was completed, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0064] Embodiment 3:
[0065] A Lewis acid coordination polymer THEED-Pd of the present invention is obtained by reacting N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine with palladium dichloride (PdCl2), and the reaction equation is:
[0066]
[0067] Among them, 5≤n≤500.
[0068] In the present invention, the preparation method of Lewis acid coordination polymer THEED-Pd is:
[0069] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless and transparent solution with a mass concentration of 2%.
[0070] (2) 1.3 mg of palladium dichloride was added to make the molar ratio of THEED to palladium dichloride be 23.1:1, and the mixture was heated and stirred at 70° C. for 5 hours to obtain a solution of the complex THEED-Pd, which was light yellow in color.
[0071] The method for preparing the Lewis acid coordination polymer THEED-Pd as a cathode modification layer is specifically as follows:
[0072] In actual operation, the 2% THEED-Pd solution was first diluted to 0.1%, and then about 70 μL of the 0.1% THEED-Pd complex was measured with a pipette and vertically dropped on the ITO conductive glass at a rotation speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0073] Embodiment 4:
[0074] A Lewis acid coordination polymer THEED-Zn of the present invention is obtained by reacting N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine with zinc acetate (Zn(CH3COO)2), and the reaction equation is:
[0075]
[0076] Among them, 5≤n≤500.
[0077] In the present invention, the preparation method of the Lewis acid coordination polymer THEED-Zn is:
[0078] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless and transparent solution with a mass concentration of 2%.
[0079] (2) 1.4 mg of zinc acetate was added to make the molar ratio of tertiary amine to zinc acetate in THEED to be 22.2:1. The mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of the complex THEED-Zn.
[0080] The method for preparing THEED-Zn Lewis acid coordination polymer as a cathode modification layer is specifically as follows:
[0081] In actual operation, the 2% THEED-Zn solution was first diluted to 0.1%, and then about 70 μL of the 0.1% THEED-Zn complex was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0082] Embodiment 5:
[0083] A Lewis acid coordination polymer THEED-Ga of the present invention is obtained by reacting N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine with gallium chloride (GaCl3), and the reaction equation is:
[0084]
[0085] Among them, 5≤n≤500.
[0086] In this embodiment, the preparation method of Lewis acid coordination polymer THEED-Ga is:
[0087] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless and transparent solution with a mass concentration of 2%.
[0088] (2) 1.3 mg of gallium chloride was added to make the molar ratio of tertiary amine to gallium chloride in THEED to be 22.9:1, and the mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of Lewis acid coordination polymer THEED-Ga.
[0089] The method for preparing the Lewis acid coordination polymer THEED-Ga as a cathode modification layer is specifically as follows:
[0090] In actual operation, the 2% THEED-Ga solution was first diluted to 0.1%, and then about 70 μL of the 0.1% THEED-Ga complex was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0091] Embodiment 6:
[0092] A Lewis acid coordination polymer BP-Ag of the present invention is obtained by reacting 1,4-bis(2-hydroxyethyl)piperazine with silver nitrate (AgNO3), and the reaction equation is:
[0093]
[0094] Among them, 5≤n≤500.
[0095] In this embodiment, the preparation method of Lewis acid coordination polymer BP-Ag is:
[0096] (1) Dissolve 40 mg of BP in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0097] (2) Add 2.6 mg of silver nitrate so that the molar ratio of BP to silver nitrate is 15:1, and heat and stir at 70° C. for 5 hours to obtain a colorless solution of Lewis acid coordination polymer BP-Ag.
[0098] The method for preparing the Lewis acid coordination polymer BP-Ag as a cathode modification layer is specifically as follows:
[0099] In actual operation, the 2% BP-Ag solution was first diluted to 0.1%, and then about 70 μL of the 0.1% complex BP-Ag was measured with a pipette and dropped vertically on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating was completed, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0100] Embodiment 7:
[0101] A Lewis acid coordination polymer HTTE-Ag of the present invention is obtained by reacting tris(2-hydroxyethyl)hexahydro-s-triazine with silver nitrate (AgNO3), and the reaction equation is:
[0102]
[0103] Among them, 5≤a≤500, 5≤b≤500.
[0104] In the present invention, the preparation method of the Lewis acid coordination polymer HTTE-Ag is:
[0105] (1) Dissolve 40 mg of HTTE in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0106] (2) 3.1 mg of silver nitrate was added to make the molar ratio of HTTE to silver nitrate be 10:1, and the mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of Lewis acid coordination polymer HTTE-Ag.
[0107] The method for preparing the Lewis acid coordination polymer HTTE-Ag as a cathode modification layer is specifically as follows:
[0108] In actual operation, the 2% HTTE-Ag solution is first diluted to 0.1%, and then about 70 μL of the 0.1% HTTE-Ag complex is measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating is completed, it is placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0109] Embodiment 8:
[0110] A Lewis acid coordination polymer PMDETA-Pt of the present invention is obtained by reacting pentamethyldiethylenetriamine with platinum dichloride (PtCl2), and the reaction equation is:
[0111]
[0112] Among them, 5≤a≤500, 5≤b≤500.
[0113] In the present invention, the preparation method of the Lewis acid coordination polymer PMDETA-Pt is:
[0114] (1) Dissolve 40 mg of PMDETA in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0115] (2) 4.6 mg of platinum dichloride was added to make the molar ratio of PMDETA to platinum dichloride be 13.4:1, and the mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of Lewis acid coordination polymer PMDETA-Pt.
[0116] The method for preparing the Lewis acid coordination polymer PMDETA-Pt as a cathode modification layer is specifically as follows:
[0117] In actual operation, the 2% PMDETA-Pt solution was first diluted to 0.1%, and then about 70 μL of the 0.1% PMDETA-Pt complex was measured with a pipette and vertically dropped on the ITO conductive glass at a rotation speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0118] Embodiment 9:
[0119] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer THEED-DBO-Pt, is obtained by reacting a polyelectrolyte THEED-DBO obtained by cross-linking N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine (THEED) and 1,8-dibromooctane (DBO) with platinum dichloride (PtCl2), and the reaction equation is:
[0120]
[0121] Among them, 5≤a≤500, 5≤b≤500.
[0122] In this embodiment, the preparation method of the metal coordination polymer THEED-DBO-Pt is:
[0123] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless and transparent solution with a mass concentration of 2%.
[0124] (2) 30 μL of 1,8-dibromooctane was added to make the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine be 1:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte THEED-DBO solution.
[0125] (3) Add 2.0 mg of platinum dichloride to the THEED-DBO solution, with the mass ratio of THEED-DBO to platinum dichloride being 42:1, and heat and stir at 70° C. for 5 hours to obtain a colorless solution of the metal coordination polymer THEED-DBO-Pt.
[0126] The method for preparing the metal coordination polymer THEED-DBO-Pt as a cathode modification layer is specifically as follows:
[0127] In actual operation, the 2% THEED-DBO-Pt solution was first diluted to 0.1%, and then about 70 μL of 0.1% THEED-DBO-Pt was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0128] Embodiment 10:
[0129] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer THEED-DBO-Ag, is obtained by reacting a polyelectrolyte THEED-DBO and silver nitrate (AgNO3), and the reaction equation is:
[0130]
[0131] Among them, 5≤a≤500, 5≤b≤500.
[0132] In this embodiment, the preparation method of the metal coordination polymer THEED-DBO-Ag is:
[0133] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0134] (2) 30 μL of 1,8-dibromooctane was added to make the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine be 1:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte THEED-DBO solution.
[0135] (3) 1.3 mg of silver nitrate was added to the THEED-DBO solution, with the mass ratio of THEED-DBO to silver nitrate being 65:1. The mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of the metal coordination polymer THEED-DBO-Ag.
[0136] The method for preparing the metal coordination polymer THEED-DBO-Ag as a cathode modification layer is specifically as follows:
[0137] In actual operation, the 2% THEED-DBO-Ag solution was first diluted to 0.1%, and then about 70 μL of the 0.1% polymer THEED-DBO-Ag was measured with a pipette and vertically dropped on the ITO conductive glass at a rotation speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0138] Embodiment 11:
[0139] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer THEED-DBO-Pd, is obtained by reacting a polyelectrolyte THEED-DBO and palladium chloride (PdCl2), and the reaction equation is:
[0140]
[0141] Among them, 5≤a≤500, 5≤b≤500.
[0142] In the present invention, the preparation method of the metal coordination polymer THEED-DBO-Pd is:
[0143] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol to obtain a colorless transparent solution with a mass concentration of 2%.
[0144] (2) 30 μL of 1,8-dibromooctane was added to make the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine be 1:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte THEED-DBO solution.
[0145] (3) Add 1.3 mg of palladium chloride to the THEED-DBO solution, with the mass ratio of THEED-DBO to palladium chloride being 65:1, and heat and stir at 70° C. for 5 hours to obtain the metal coordination polymer THEED-DBO-Pd. The color of the solution is golden yellow.
[0146] The method for preparing the metal coordination polymer THEED-DBO-Pd as a cathode modification layer is specifically as follows:
[0147] In actual operation, the 2% THEED-DBO-Pd solution was first diluted to 0.1%, and then about 70 μL of 0.1% polymer THEED-DBO-Pd was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0148] Embodiment 12:
[0149] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer THEED-DBO-Zn, is obtained by reacting a polyelectrolyte THEED-DBO and zinc acetate (Zn(CH3COO)2), and the reaction equation is:
[0150]
[0151] Among them, 5≤a≤500, 5≤b≤500.
[0152] In the present invention, the preparation method of the metal coordination polymer THEED-DBO-Zn is:
[0153] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0154] (2) 30 μL of 1,8-dibromooctane was added to make the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine be 1:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte THEED-DBO solution.
[0155] (3) 1.4 mg of zinc acetate was added to the THEED-DBO solution, with the mass ratio of THEED-DBO to zinc acetate being 60:1. The mixture was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of the metal coordination polymer THEED-DBO-Zn.
[0156] The method for preparing the metal coordination polymer THEED-DBO-Zn as a cathode modification layer is specifically as follows:
[0157] In actual operation, the 2% THEED-DBO-Zn solution was first diluted to 0.1%, and then about 70 μL of the 0.1% metal coordination polymer THEED-DBO-Zn was measured with a pipette and vertically dropped on the ITO conductive glass at a rotation speed of 5000 rpm. The spin coating time was 50 seconds. After the spin coating was completed, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0158] Embodiment 13:
[0159] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer THEED-DBO-Ga, is obtained by reacting a polyelectrolyte THEED-DBO and gallium chloride (GaCl3), and the reaction equation is:
[0160]
[0161] Among them, 5≤a≤500, 5≤b≤500.
[0162] In the present invention, the preparation method of the metal coordination polymer THEED-DBO-Ga is as follows:
[0163] (1) Dissolve 40 mg of THEED in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0164] (2) 30 μL of 1,8-dibromooctane was added to make the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine be 1:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte THEED-DBO solution.
[0165] (3) Add 1.3 mg of gallium chloride to the THEED-DBO solution, with the mass ratio of THEED-DBO to gallium chloride being 65:1, and heat and stir at 70° C. for 5 hours to obtain a colorless solution of the polymer THEED-DBO-Ga.
[0166] The method for preparing the metal coordination polymer THEED-DBO-Ga as a cathode modification layer is specifically as follows:
[0167] In actual operation, the 2% THEED-DBO-Ga solution was first diluted to 0.1%, and then about 70 μL of the 0.1% THEED-DBO-Ga solution was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0168] Embodiment 14:
[0169] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer PEDETA-DBO-Pt, is obtained by reacting a polyelectrolyte PEDETA-DBO and platinum dichloride (PtCl2), and the reaction equation is:
[0170]
[0171] Among them, 5≤a≤500, 5≤b≤500.
[0172] In the present invention, the preparation method of the metal coordination polymer PEDETA-DBO-Pt is:
[0173] (1) Dissolve 40 mg of PEDETA in 2 mL of 2-methoxyethanol and stir at room temperature to disperse it evenly to obtain a colorless transparent solution with a mass concentration of 2%.
[0174] (2) 34 μL of 1,8-dibromooctane was added to make the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine be 1.5:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte PEDETA-DBO solution.
[0175] (3) Add 2.2 mg of platinum dichloride to the PEDETA-DBO solution, the mass ratio of PEDETA-DBO to platinum dichloride is 41:1, and heat and stir at 70° C. for 5 hours to obtain a colorless solution of the metal coordination polymer PEDETA-DBO-Pt.
[0176] The method for preparing the metal coordination polymer PEDETA-DBO-Pt as a cathode modification layer is specifically as follows:
[0177] In actual operation, the 2% PEDETA-DBO-Pt solution was first diluted to 0.1%, and then about 70 μL of the 0.1% PEDETA-DBO-Pt solution was measured with a pipette and vertically dropped on the ITO conductive glass at a rotation speed of 5000 rpm for 50 seconds. After the spin coating, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0178] Embodiment 15:
[0179] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer PEIE-DBO-Pt, is obtained by reacting a polyelectrolyte PEIE-DBO and platinum dichloride (PtCl2), and the reaction equation is:
[0180]
[0181] Among them, 5≤a≤500, 5≤b≤500.
[0182] In the example of the present invention, the preparation method of the metal coordination polymer PEIE-DBO-Pt is:
[0183] (1) Take 40 mg of a 35% to 40% by weight polyethoxyethyleneimine (PEIE) aqueous solution, add 10 mL of 2-methoxyethanol, so that the mass concentration of polyethoxyethyleneimine in the resulting mixed solution is about 0.15%, and stir at room temperature to disperse it evenly to obtain a colorless transparent solution.
[0184] (2) 12 μL of 1,8-dibromooctane was added to make the mass ratio of 1,8-dibromooctane to polyethoxyethyleneimine be 1.2:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a colorless solution, i.e., a polyelectrolyte PEIE-DBO solution.
[0185] (3) 1.5 mg of platinum dichloride was added to the PEIE-DBO solution, with the mass ratio of PEIE-DBO to platinum dichloride being 22:1. The solution was heated and stirred at 70° C. for 5 hours to obtain a colorless solution of the metal coordination polymer PEIE-DBO-Pt.
[0186] The method for preparing the metal coordination polymer PEIE-DBO-P as a cathode modification layer is specifically as follows:
[0187] In actual operation, first use a pipette to measure about 70 μL of PEIE-DBO-Pt solution with a mass concentration of about 0.15%, and drop it vertically on the ITO conductive glass rotating at a speed of 5000 rpm, and the spin coating time is 50 seconds. After the spin coating is completed, it is placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0188] Embodiment 16:
[0189] A Lewis acid coordination polymer of the present invention, specifically a metal coordination polymer PEIE-MSB-Pt, is obtained by reacting a polyelectrolyte PEIE-MSB and platinum dichloride (PtCl2), and the reaction equation is:
[0190]
[0191] Among them, 5≤a≤500, 5≤b≤500.
[0192] In the present invention, the preparation method of the metal coordination polymer PEIE-MSB-Pt is:
[0193] (1) Take 40 mg of a 35% to 40% by weight polyethoxyethyleneimine (PEIE) aqueous solution, add 10 mL of 2-methoxyethanol to make the mass concentration of polyethoxyethyleneimine about 0.15%, and stir at room temperature to disperse it evenly to obtain a colorless transparent solution.
[0194] (2) 18 mg of 1,4-butanediol dimethanesulfonate was added so that the mass ratio of 1,4-butanediol dimethanesulfonate to polyethoxyethyleneimine was 1.2:1, and the mixture was heated and stirred at 70° C. for 24 hours to obtain a light yellow polyelectrolyte PEIE-MSB solution.
[0195] (3) 1.5 mg of platinum dichloride was added to the PEIE-MSB solution, with the mass ratio of PEIE-MSB to platinum dichloride being 22:1. The solution was heated and stirred at 70° C. for 5 hours to obtain a light yellow solution of the metal coordination polymer PEIE-MSB-Pt.
[0196] The method for preparing the metal coordination polymer PEIE-MSB-Pt as a cathode modification layer is specifically as follows:
[0197] In actual operation, about 70 μL of PEIE-MSB-Pt solution with a mass concentration of about 0.15% was measured with a pipette and vertically dropped on the ITO conductive glass rotating at a speed of 5000 rpm, and the spin coating time was 50 s. After the spin coating was completed, it was placed on a heating table at 100°C for 10 minutes to obtain a cathode modification layer coated on the ITO conductive glass.
[0198] Comparative Example 1:
[0199] A method for preparing a zinc oxide cathode modification layer:
[0200] 1.00 g of zinc acetate dihydrate was weighed, 10 mL of 2-methoxyethanol and 272 μL of ethanolamine were added, and then stirred at room temperature for 10 hours to obtain a zinc oxide precursor solution. The zinc oxide precursor solution was spin-coated onto a clean ITO conductive glass sheet treated with ozone for 15 minutes at a speed of 3500 rpm, and then annealed at 220° C. in air for 30 minutes to obtain a cathode covered with a zinc oxide cathode modification layer, and the film thickness of zinc oxide was about 30 nm.
[0201] Comparative Example 2:
[0202] A method for preparing a polyelectrolyte THEED-DBO cathode modification layer:
[0203] Take 40mg THEED and dissolve it in 2mL 2-methoxyethanol, stir at room temperature to disperse it evenly, and obtain a colorless transparent solution with a mass concentration of 2%. Then add 30μL 1,8-dibromooctane, so that the molar ratio of 1,8-dibromooctane to N,N,N,N-tetrakis(2-hydroxyethyl)ethylenediamine is 1:1, and heat and stir at 70℃ for 24 hours to obtain a polyelectrolyte THEED-DBO solution. In actual operation, first dilute the THEED-DBO solution with a mass concentration of 2% to 0.1%, then use a pipette to measure about 70μL of the THEED-DBO solution with a concentration of 0.1%, and drop it vertically on the ITO conductive glass with a rotation speed of 5000 rpm, and the spin coating time is 50s. After the spin coating is completed, place it on a heating table at 100℃ and heat it for 10 minutes to obtain the THEED-DBO cathode modification layer coated on the ITO conductive glass.
[0204] Comparative Example 3:
[0205] A method for preparing a polyelectrolyte PEDETA-DBO cathode modification layer:
[0206] Take 40mg of penta(2-hydroxyethyl)diethylenetriamine (PEDETA) and dissolve it in 2mL of 2-methoxyethanol, stir at room temperature to disperse it evenly, and obtain a colorless transparent solution with a mass concentration of 2%. Then add 34μL of 1,8-dibromooctane so that the molar ratio of 1,8-dibromooctane to penta(2-hydroxyethyl)diethylenetriamine is 1.5:1, and heat and stir at 70℃ for 24 hours to obtain a polyelectrolyte PEDETA-DBO solution. Dilute the 2% PEDETA-DBO solution to 0.1%, and then use a pipette to measure about 70μL of the 0.1% PEDETA-DBO solution, and drop it vertically on the ITO conductive glass with a rotation speed of 5000 rpm, and the spin coating time is 50s. After the spin coating is completed, place it on a heating table at 100℃ and heat it for 10 minutes to obtain a PEDETA-DBO cathode modification layer coated on the ITO conductive glass.
[0207] Comparative Example 4:
[0208] A method for preparing a polyelectrolyte PEIE-DBO cathode modification layer:
[0209] Take 40 mg of 35% to 40% polyethoxyethyleneimine PEIE aqueous solution, add 10 mL of 2-methoxyethanol, so that the mass concentration of polyethoxyethyleneimine in the obtained mixed solution is about 0.15%, stir at room temperature to disperse it evenly, and obtain a colorless and transparent solution. Then add 12 μL of 1,8-dibromooctane, so that the mass ratio of 1,8-dibromooctane to polyethoxyethyleneimine is 1.2:1, and heat and stir at 70°C for 24 hours to obtain a polyelectrolyte PEIE-DBO solution. Use a pipette to measure about 70 μL of PEIE-DBO solution, drop it vertically on the ITO conductive glass with a rotation speed of 5000 rpm, and the spin coating time is 50s. After the spin coating is completed, place it on a heating table at 100°C and heat for 10 minutes to obtain a PEIE-DBO cathode modification layer coated on the ITO conductive glass.
[0210] Comparative Example 5:
[0211] A method for preparing a polyelectrolyte PEIE-MSB cathode modification layer:
[0212] Take 40 mg of 35%-40% polyethoxyethyleneimine PEIE aqueous solution, add 10 mL of 2-methoxyethanol, so that the mass concentration of polyethoxyethyleneimine in the obtained mixed solution is about 0.15%, stir at room temperature to disperse it evenly, and obtain a colorless and transparent solution. Then add 18 mg of 1,4-butanediol dimethanesulfonate (MSB) so that the mass ratio of 1,4-butanediol dimethanesulfonate to polyethoxyethyleneimine is 1.2:1, and heat and stir at 70°C for 24 hours to obtain a polyelectrolyte PEIE-MSB solution. Use a pipette to measure about 70 μL of PEIE-MSB solution, drop it vertically on the ITO conductive glass with a rotation speed of 5000 rpm, and the spin coating time is 50s. After the spin coating is completed, place it on a heating table at 100°C and heat for 10 minutes to obtain a PEIE-MSB cathode modification layer coated on the ITO conductive glass.
[0213] Experimental Example 1: Preparation and characterization of OSCs devices.
[0214] The THEED-Pt cathode modification layer prepared in Example 1, the THEED-Ag cathode modification layer prepared in Example 2, the THEED-Pd cathode modification layer prepared in Example 3, the THEED-Zn cathode modification layer prepared in Example 4, the THEED-Ga cathode modification layer prepared in Example 5, the BP-Ag cathode modification layer prepared in Example 6, the HTTE-Ag cathode modification layer prepared in Example 7, the PMDETA-Pt cathode modification layer prepared in Example 8, the THEED-DBO-Pt cathode modification layer prepared in Example 9, the THEED-DBO-Ag cathode modification layer prepared in Example 10, the THEED-DBO-Pd cathode modification layer prepared in Example 11, and the A reverse organic solar cell (OSCs) device was prepared under the same conditions using an ITO electrode covered with THEED-DBO-Zn cathode modification layer, a THEED-DBO-Ga cathode modification layer prepared in Example 13, a PEDETA-DBO-Pt cathode modification layer prepared in Example 14, a PEIE-DBO-Pt cathode modification layer prepared in Example 15, a PEIE-MSB-Pt cathode modification layer prepared in Example 16, a ZnO cathode modification layer prepared in Comparative Example 1, a THEED-DBO cathode modification layer prepared in Comparative Example 2, a PEDETA-DBO cathode modification layer prepared in Comparative Example 3, a PEIE-DBO cathode modification layer prepared in Comparative Example 4 and a PEIE-MSB cathode modification layer prepared in Comparative Example 5.
[0215] The application of the above cathode modification layer in the reverse OSCs device can be adopted in the following manner: first, the cathode modification layer prepared in this embodiment is applied to a clean ITO conductive glass, and then the organic photoactive layer (a mixed film of polymer donor material and non-fullerene acceptor material) is continuously applied on the cathode modification layer prepared in this embodiment, and then the anode modification layer (also called hole transport layer or hole extraction layer) is evaporated, and finally the metal electrode is evaporated to obtain the reverse OSCs device. The polymer donor material, acceptor material, anode modification layer and metal electrode of OSCs all use materials and preparation methods known to those skilled in the art. Among them, the polymer donor material is PM6, which was purchased from Shuo Lun Organic Optoelectronics Technology (Beijing) Co., Ltd.; the acceptor materials are Y6, IT-4F, L8-BO, BTP-eC9-4Cl, which were purchased from Shenzhen Yirou Photovoltaic Technology Co., Ltd.
[0216] The prepared OSCs device was exposed to AM 1.5G simulated sunlight (100 mW cm -2 ) were used to test its photovoltaic performance, and the photovoltaic performance parameters of its OSCs devices are listed in Table 1.
[0217] Table 1: Photovoltaic parameters of inverted OSCs based on different cathode modification layers (ITO / ETLs / PM6∶Y6 / MoO3 / Al)
[0218]
[0219]
[0220] As can be seen from Table 1, the photoelectric conversion efficiency (PCE) of the OSCs using the Lewis acid coordination polymer THEED-Pt of Example 1 of the present invention as the cathode modification layer is 17.17%, which is 12.08% higher than that of the OSCs using the THEED without the coordinated Lewis acid as the cathode modification layer, and 11.49% higher than that of the OSCs using the ZnO (Comparative Example 1) as the cathode modification layer under the same conditions; the photoelectric conversion efficiency of the OSCs using the Lewis acid coordination polymer THEED-Ag of Example 2 as the cathode modification layer is 16.59%, which is 7.73% higher than that of the OSCs using the ZnO (Comparative Example 1) as the cathode modification layer under the same conditions; the photoelectric conversion efficiency of the OSCs using the Lewis acid coordination polymer THEED-Pd of Example 3 as the cathode modification layer is 16.61%, which is 16.61% higher than that of the OSCs using the ZnO (Comparative Example 1) as the cathode modification layer under the same conditions. Compared with OSCs with ZnO (Comparative Example 1) as cathode modification layer, the photoelectric conversion efficiency of OSCs is relatively improved by 7.86%; the photoelectric conversion efficiency of OSCs using the Lewis acid coordination polymer THEED-Zn of Example 4 as cathode modification layer is 16.82%, which is 9.22% higher than that of OSCs with ZnO (Comparative Example 1) as cathode modification layer under the same conditions; the photoelectric conversion efficiency of OSCs using the Lewis acid coordination polymer THEED-Ga of Example 5 as cathode modification layer is 17.38%, which is 12.86% higher than that of OSCs with ZnO (Comparative Example 1) as cathode modification layer under the same conditions; the photoelectric conversion efficiency of OSCs using the Lewis acid coordination polymer BP-Ag of Example 6 as cathode modification layer is 16.51%, which is 7.2% higher than that of OSCs with ZnO (Comparative Example 1) as cathode modification layer under the same conditions. The photoelectric conversion efficiency of OSCs using the Lewis acid coordination polymer HTTE-Pt of Example 7 as the cathode modification layer is 16.58%, which is 7.7% higher than that of OSCs using ZnO (Comparative Example 1) as the cathode modification layer under the same conditions. The photoelectric conversion efficiency of OSCs using the Lewis acid coordination polymer PMDETA-Pt of Example 8 as the cathode modification layer is 16.16%, which is 11.60% higher than that of OSCs using PMDETA without Lewis acid as the cathode modification layer, and 4.9% higher than that of OSCs using ZnO (Comparative Example 1) as the cathode modification layer under the same conditions. The results show that the introduction of different metal ion Lewis acids into THEED, BP, HTTE, and PMDETA will cause the tertiary amines therein to coordinate with different metal ions to form Lewis acid coordination polymers, which can improve device performance.The Lewis acid coordination polymers of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Example 7, and Example 8 of the present invention all improve the charge collection efficiency to varying degrees, and the device performance is improved.
[0221] Compared with the same period last year, the photoelectric conversion efficiency of the OSCs using the metal coordination polymer THEED-DBO-Pt as the cathode modification layer of Example 9 of the present invention is 17.63%, which is 9.10% higher than that of the OSCs using THEED-DBO (Comparative Example 2) as the cathode modification layer under the same conditions, and 14.48% higher than that of the OSCs using ZnO (Comparative Example 1) as the cathode modification layer under the same conditions; The photoelectric conversion efficiency of OSCs using the metal coordination polymer THEED-DBO-Pd of Example 11 of the present invention as the cathode modification layer is 17.27%, which is 3.65% higher than that of OSCs using THEED-DBO (Comparative Example 2) as the cathode modification layer under the same conditions, and 8.76% higher than that of OSCs using ZnO (Comparative Example 1) as the cathode modification layer under the same conditions. Compared with the OSCs with the cathode modification layer based on ZnO (Comparative Example 1) as the cathode modification layer under the same conditions, the photoelectric conversion efficiency is relatively increased by 6.87%, and compared with the OSCs with ZnO (Comparative Example 1) as the cathode modification layer under the same conditions, the photoelectric conversion efficiency is relatively increased by 12.14%; the photoelectric conversion efficiency of the OSCs with the metal coordination polymer THEED-DBO-Zn as the cathode modification layer of Example 12 of the present invention is 16.99%, and compared with the OSCs with THEED-DBO (Comparative Example 2) as the cathode modification layer under the same conditions, the photoelectric conversion efficiency is relatively increased by 5.14%, and compared with the OSCs with ZnO (Comparative Example 3) as the cathode modification layer under the same conditions, the photoelectric conversion efficiency is relatively increased by 1.2%. Compared with OSCs with ZnO (Comparative Example 1) as cathode modification layer, its photoelectric conversion efficiency is relatively improved by 10.32%; the photoelectric conversion efficiency of OSCs with the metal coordination polymer THEED-DBO-Ga of Example 13 of the present invention as cathode modification layer is 17.44%, compared with OSCs with THEED-DBO (Comparative Example 2) as cathode modification layer under the same conditions, its photoelectric conversion efficiency is respectively improved by 7.92%, and compared with OSCs with ZnO (Comparative Example 1) as cathode modification layer under the same conditions, its photoelectric conversion efficiency is relatively improved by 13.25%. Similarly, compared with the polyelectrolyte (THEED-DBO) of Comparative Example 2, the Lewis acid coordination polymer coordinated by different Lewis acids can be well matched with the electrode, reduce the energy barrier, be more conducive to the transmission of electrons, and improve the photoelectric conversion efficiency of OSCs.
[0222] The photoelectric conversion efficiency of OSCs using the metal coordination polymer PEDETA-DBO-Pt of Example 14 of the present invention as the cathode modification layer is 16.58%, which is 7.66% higher than that of OSCs using PEDETA-DBO (Comparative Example 3) as the cathode modification layer under the same conditions, and 7.66% higher than that of OSCs using ZnO (Comparative Example 1) as the cathode modification layer under the same conditions; the photoelectric conversion efficiency of OSCs using the metal coordination polymer PEIE-DBO-Pt of Example 15 of the present invention as the cathode modification layer is 16.88%, which is 16.86% higher than that of OSCs using PEIE-DBO (Comparative Example 4) as the cathode modification layer under the same conditions. Compared with OSCs with cathode modification layer as cathode modification layer, its photoelectric conversion efficiency is increased by 4.00% respectively, and compared with OSCs with ZnO (Comparative Example 1) as cathode modification layer under the same conditions, its photoelectric conversion efficiency is relatively increased by 9.61%; when the metal coordination polymer PEIE-MSB-Pt of Example 16 of the present invention is used as the cathode modification layer of OSCs, its photoelectric conversion efficiency is 16.06%, compared with OSCs with PEIE-MSB (Comparative Example 5) as cathode modification layer under the same conditions, its photoelectric conversion efficiency is respectively increased by 4.76%, and compared with OSCs with ZnO (Comparative Example 1) as cathode modification layer under the same conditions, its photoelectric conversion efficiency is relatively increased by 4.29%. By utilizing metal ion Lewis acid coordination to form other metal coordination polymers, they can be well matched with electrodes, reduce energy barriers, be more conducive to the transmission of electrons, and improve the photoelectric conversion efficiency of OSCs.
[0223] Experimental Example 2: Universality
[0224] The Lewis acid coordination polymer THEED-DBO-Pt of Example 9 of the present invention was used as the cathode modification layer of OSCs. -2 ), the photovoltaic performance of OSCs based on different photoactive layers was investigated. The preparation method and other parameters were the same as those in Experimental Example 1. The current density-voltage (JV) curve of the OSCs device is shown in Figure 1 and Figure 2 , the photovoltaic parameters are listed in Table 2 and Table 3.
[0225] Table 2: Photovoltaic parameters of inverse non-fullerene OSCs based on THEED-DBO-Pt (Example 9) (ITO / THEED-DBO-Pt / active layer / MoO3 / Al)
[0226]
[0227]
[0228] Depend on Figure 1 It can be seen from the data in Table 2 that the Lewis acid coordination polymer THEED-DBO-Pt in Example 9 of the present invention is used as the cathode modification layer of OSCs, and excellent photoelectric conversion efficiency is shown in different reverse non-fullerene systems. Among them, the photoelectric conversion efficiency of the prepared reverse OSCs device using PM6 as the donor material and IT-4F as the acceptor material is 13.68%. The photoelectric conversion efficiency of the prepared reverse OSCs device using PM6 as the donor material and Y6 as the acceptor material is 17.63%. The photoelectric conversion efficiency of the prepared reverse OSCs device using PM6 as the donor material and BTP-eC9-4Cl as the acceptor material is 17.95%. The photoelectric conversion efficiency of the prepared reverse OSCs device using PM6 as the donor material and L8-BO as the acceptor material is 18.12%. From the photovoltaic performance parameters of the above OSCs, it can be seen that THEED-DBO-Pt exhibits excellent device performance in trans non-fullerene OSCs, and its photoelectric conversion efficiency is better than that of OSCs prepared with ZnO and PFN-Br as cathode modification layers reported in the literature《Joule, 2019, 3, 1140-1151》《Adv. Mater., 2020, 32, 1908205》《Nature Energy, 2021, 6, 605-613》. This result shows that the metal coordination polymer THEED-DBO-Pt has good universality in non-fullerene OSCs and is an excellent cathode modification layer material.
[0229] Table 3: Photovoltaic parameters of forward non-fullerene OSCs based on THEED-DBO-Pt (Example 9) (ITO / PEDOT:PSS / active layer / THEED-DBO-Pt / Al)
[0230]
[0231] Depend on Figure 2From the data in Table 3, it can be seen that the use of the polymer THEED-DBO-Pt in Example 9 of the present invention as the cathode modification layer of OSCs also shows good photoelectric conversion efficiency in different forward non-fullerene OSCs. Using PM6 as the donor material and BTP-eC9-4Cl as the acceptor material, the photoelectric conversion efficiency of the prepared forward OSCs device is 17.13%. Using PM6 as the donor material and L8-BO as the acceptor material, the photoelectric conversion efficiency of the prepared forward OSCs device is 17.57%. It is found through the chart data that the metal coordination polymer THEED-DBO-Pt as the cathode modification layer of OSCs has a slightly lower performance in the forward device than in the reverse device, but can still reach more than 95% of the best performance of the trans device. This result shows that the metal coordination polymer THEED-DBO-Pt of the present invention exhibits excellent performance regardless of the forward device structure or the trans device structure.
[0232] Experimental Example 3: Thickness Tolerance
[0233] The polymer THEED-DBO-Pt in Example 9 was used as the cathode modification layer of OSCs, and reverse OSCs devices with different thicknesses were prepared to investigate the effects of cathode modification layers of different thicknesses on the photovoltaic performance of the devices. The other conditions were the same as those in Experimental Example 1.
[0234] The prepared inverted OSCs device was exposed to AM 1.5G simulated sunlight (100 mW cm -2 ) to test its photovoltaic performance, and the current density-voltage (JV) curve of its OSCs device is shown in Figure 3 , the photovoltaic parameters are listed in Table 4.
[0235] Table 4: Photovoltaic parameters of inverse OSCs based on different thicknesses of THEED-DBO-Pt (Example 9) (ITO / THEED-DBO-Pt / PM6:Y6 / MoO3 / Al)
[0236]
[0237] from Figure 3From the results in Table 4, it can be seen that the polymer THEED-DBO-Pt in Example 9 of the present invention is used as the cathode modification layer of OSCs, PM6 is used as the donor material, and Y6 is used as the acceptor material to prepare a trans device. When the thickness of the THEED-DBO-Pt polymer is 6nm, the photoelectric conversion efficiency of its OSCs is 16.49%, which does not reach the optimal efficiency. This is because the thickness of the THEED-DBO-Pt film is too thin and there are defects on the surface. When the thickness of the THEED-DBO-Pt film increases to 11nm, the surface defects decrease, and the photoelectric conversion efficiency of its OSCs reaches a maximum value of 17.63%. As the thickness of the THEED-DBO-Pt film continues to increase, the photoelectric conversion efficiency decreases again. This is because the continuous increase in the film thickness will cause the series resistance of the OSCs to gradually increase, resulting in a gradual decrease in the short-circuit current density and filling factor of the OSCs, and the photoelectric conversion efficiency also gradually decreases. When the film thickness of THEED-DBO-Pt is 47nm, the photoelectric conversion efficiency of its OSCs is 16.56%, which can still retain 94% of the best photovoltaic performance. This result shows that the metal coordination polymer THEED-DBO-Pt in Example 9 of the present invention has excellent thickness tolerance and has a good application prospect.
[0238] Experimental Example 4: Stability
[0239] The stability of the device is an issue that must be considered for the commercial development of the photovoltaic field. The Lewis acid coordination polymer THEED-DBO-Pt of Example 9 of the present invention, ZnO in Comparative Example 1, and the polyelectrolyte THEED-DBO in Comparative Example 2 were used as the cathode modification layer of the reverse OSCs to investigate their storage stability. The preparation method and other parameters were the same as those in Experimental Example 1, and the storage method was to place it in a glove box filled with nitrogen without packaging. The current density-voltage (JV) curve of the OSCs device is shown in Figure 4 .from Figure 4 It can be seen that the performance of the devices modified by the above three materials has declined with the extension of time. The OSCs devices prepared with ZnO and THEED-DBO can only maintain about 75% of the initial value after storage for 90 days (not encapsulated, stored in a glove box filled with nitrogen), and the PCE after storage for 250 days is only about 55%. The OSCs devices prepared with THEED-DBO-Pt still maintain more than 85% of the initial value after storage for 90 days, and can still maintain 78% of the initial value after storage for 250 days. The results show that under the same conditions, OSCs prepared with metal coordination polymers exhibit better reserve stability. This is because the metal ion Pt 2+The empty orbital of the tertiary amine can coordinate with the lone pair of electrons in the tertiary amine, reducing the content of tertiary amine in the cathode modification layer, effectively inhibiting the degradation process of the non-fullerene receptor induced by the tertiary amine unit, and making the device performance more stable.
[0240] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. For those skilled in the art, without departing from the principle and technical solution of the present invention, many possible improvements and modifications can be made to the technical solution of the present invention, or modified into equivalent embodiments of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing a Lewis acid coordination polymer, characterized in that: The Lewis acid coordination polymer is obtained by reacting a polyelectrolyte containing both amine and quaternary ammonium salt functional groups with a Lewis acid; The polyelectrolyte comprises one or more of the following formulas X, XI, XII and XIII, , Wherein, CA is selected from one or more alkanes having 2 to 15 carbon atoms or alkanes containing aromatic rings, and X - is selected from one or more of fluoride, chloride, bromide, iodide, sulfonate, acetate, sulfate, carbonate, nitrate, phosphate and hydroxide, R is selected from one or more of H, CH3, CH2CH3, CH2OH and C2H4OH, R1 is selected from one of H, CH2CH2NH2 and CH2CH2OH, R2 is selected from one of H, CH2CH2NH2 and CH2CH2OH, R3 is selected from one of H, CH2CH2NH2 and CH2CH2OH, 5≤a≤500, 5≤b≤500; The Lewis acid refers to a metal ion compound that can form a coordination bond with the lone pair of electrons on the nitrogen atom in the amine derivative and has an empty orbital. The structural formula of the Lewis acid is ML z , M.L. z Selected from PtCl2, AgNO3, PdCl2, Zn(CH3COO)2 or GaCl3; The molecular structure of the Lewis acid coordination polymer includes one or more of the structural formulas shown in formula (VI), formula (VII), formula (VIII) and formula (IX); , 。 2. The method for preparing a Lewis acid coordination polymer according to claim 1, characterized in that: The following steps are involved: S1. First, prepare an alcohol solution of a polyelectrolyte of formula X, formula XI, formula XII or formula XIII, wherein the alcohol solvent used is methanol, ethanol, 2-methoxyethanol, 1-propanol, isopropanol, 1-butanol and t - one or more of tert-butyl alcohol; S2. Add Lewis acid to the alcohol solution of the polyelectrolyte obtained in S1, and stir the reaction at 40° C. to 90° C. for 4 h to 72 h to obtain a final Lewis acid coordination polymer solution.
3. The method for preparing a Lewis acid coordination polymer according to claim 2, characterized in that: The mass fraction of the polyelectrolyte is 0.01% to 5%; the mass ratio of the polyelectrolyte to the Lewis acid is 100:0.1-100.
4. A Lewis acid coordination polymer obtained by the preparation method according to any one of claims 1 to 3.
5. Use of the Lewis acid coordination polymer prepared by the preparation method according to any one of claims 1 to 3 in an organic solar cell or a perovskite solar cell.
6. The use according to claim 5, characterized in that When the organic solar cell is an inverted organic solar cell, the application comprises the following steps: applying the Lewis acid coordination polymer dissolved or diluted in an alcohol solvent on a transparent conductive electrode by spin coating, heating at a temperature of 50 to 120° C. for 5 to 10 minutes or heating at 10 -2 ~10 2 Pa conditions for 0.5 to 3 hours to obtain an electrode coated with a cathode modification layer; further coating a photoactive layer material and an anode modification layer on the cathode modification layer; and then coating a metal electrode by evaporation to finally obtain a reverse organic solar cell; When the organic solar cell is a forward organic solar cell, the application comprises the following steps: applying a photoactive layer material to a transparent conductive electrode modified by an anode modification layer, then applying a Lewis acid coordination polymer dissolved or diluted in an alcohol solvent to the photoactive layer material by spin coating as a cathode modification layer, -2 ~10 2 Pa conditions for 0.5 to 3 hours to remove the alcohol solvent, and then evaporate the metal electrode to obtain a forward organic solar cell.
7. The use according to claim 5, characterized in that The preparation of perovskite solar cells includes the following steps: The coordination polymer dissolved or diluted in an alcohol solvent is applied on the transparent conductive electrode by spin coating, and heated at 50 to 120° C. for 5 to 10 minutes or at 10 -2 ~10 2 Pa conditions for 0.5 to 3 hours to obtain an electrode modified with a cathode modification layer; coating a perovskite photoactive layer on the modified cathode, and then coating an anode modification layer and evaporating a metal electrode to obtain a nip-type perovskite solar cell; Alternatively, the preparation of the perovskite solar cell includes the following steps: coating the perovskite photoactive layer material on a transparent conductive electrode modified with an anode modification layer, then coating the cathode modification layer material dissolved or diluted with an alcohol solvent on the active layer material by spin coating or printing, and evaporating a metal electrode to obtain a pin-type perovskite solar cell.
Citation Information
Patent Citations
Negative electrode modification layer and preparation method and application thereof
CN107546328A
Reticular polymer, preparation method and applications thereof
CN111087614A
Polyelectrolytes, their preparation methods and applications
CN111154098B
Polymer-metal chelate cathode interface material and application thereof
CN111081885A